2019
DOI: 10.15394/ijaaa.2019.1360
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Aviation Pilots: Analyses of Fatigue Related Decision-Making Scenarios

Abstract: The researchers of the current study would like to thank the participants and organization for the feedback and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 25 publications
1
21
1
1
Order By: Relevance
“…As stated earlier in this paper, the Collegiate Aviation Fatigue Inventory (CAFI) was a modified version of a survey published by McDale and Ma (2008). Data from CAFI-I was instrumental in the publication of three scholarly papers (Keller et al, 2019;Levin et al, 2019;. During its development, the CAFI underwent content validity checks by six Subject-Matter Experts (SMEs) .…”
Section: Research Instrumentmentioning
confidence: 99%
“…As stated earlier in this paper, the Collegiate Aviation Fatigue Inventory (CAFI) was a modified version of a survey published by McDale and Ma (2008). Data from CAFI-I was instrumental in the publication of three scholarly papers (Keller et al, 2019;Levin et al, 2019;. During its development, the CAFI underwent content validity checks by six Subject-Matter Experts (SMEs) .…”
Section: Research Instrumentmentioning
confidence: 99%
“…Seventy-eight percent of the participants reported they committed errors and did not always give their best effort during flight training activities due to fatigue. Keller et al (2019) presented participants with six vignettes on flight scenarios which entailed sleep deprivations, stress, mental and physical fatigue.…”
Section: Fatigue In Collegiate Aviationmentioning
confidence: 99%
“…The qualitative analysis in the Keller et al (2019) study found that some participants struggled to communicate desirable alternatives, lacked knowledge of the human limitations, and expressed succumbing to external pressures such as staying on schedule to finish their flight course. However, during other scenarios some responses articulated desirable decision-making processes and expressed viable alternatives.…”
Section: Fatigue In Collegiate Aviationmentioning
confidence: 99%
See 2 more Smart Citations